2018
DOI: 10.1055/s-0038-1672197
|View full text |Cite
|
Sign up to set email alerts
|

Immune and Antioxidant Enzyme Response of Longfin Yellowtail (Seriola rivoliana) Juveniles to Ultra-diluted Substances Derived from Phosphorus, Silica and Pathogenic Vibrio

Abstract: Background This research aimed to observe the effect of homeopathic treatments prepared from Vibrio parahaemolyticus and V. alginolyticus (H1) and commercial homeopathic medication Phosphoricum acidum and Silicea terra (H2) on the immune and antioxidant response in Seriola rivoliana juveniles under usual culture conditions and challenged with V. parahaemolyticus. Materials and Methods Quantitative polymerase chain reaction analysis was used to study changes in the expression of key genes related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 77 publications
0
33
0
4
Order By: Relevance
“…In this study, HDIC regulated transcripts associated to recognition of non-self-molecules and internalisation of particles suggested that HDIC were not able to trigger all the immune response mechanisms due their high dilution. This result may explain those [61] in organisms of S. rivoliana treated with HDIC where only the genes IL-1β and MyD88 up-regulate before the challenge with V. parahaemolyticus. The results in this study suggested that the non-self-recognition system activation by effect of HDIC improved the response against infections.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this study, HDIC regulated transcripts associated to recognition of non-self-molecules and internalisation of particles suggested that HDIC were not able to trigger all the immune response mechanisms due their high dilution. This result may explain those [61] in organisms of S. rivoliana treated with HDIC where only the genes IL-1β and MyD88 up-regulate before the challenge with V. parahaemolyticus. The results in this study suggested that the non-self-recognition system activation by effect of HDIC improved the response against infections.…”
Section: Discussionmentioning
confidence: 90%
“…The effectiveness of the use of HDIC in bivalves to improve their survival against pathogen infection challenges has been widely demonstrated, our work team has proven that the application of HDIC formulated with scorpion venom, Phosphoric acid1, Silicea terra1, sodium metasilicate and Vibrio lysate (V. alginoliticus-V. parahemolityics) strengthened marine organisms (bivalves, fish and shrimp) self-defense, allowing them to survive infection challenges, reduce parasite proliferation, increase energy reserves and growth; even some of them outperformed antibiotics when they were used prophylactically in A. ventricosus culture [20,21,61,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,40,41 The studies described above have all been performed under highly controlled conditions, using milliliter volumes of liquids, as is usually the case in laboratory-based work. Considering that highly diluted preparations are also used in agriculture and on large farms devoted to cattle, broiler, and fish breeding, [26][27][28][29][30][31][32][33][34] the question then arises: could these dilutions also be effective in much larger water volumes? Empirical observations indicate that the addition of high diluted products to drinking and irrigation water sources can spread the action of such dilutions over large farm areas and cause specific effects in substantial numbers of individual animals at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…23 Discovering if solvatochromic dyes are sensitive enough to detect changes in the polarity of large water volumes would be a critical step in evaluating the plausibility of using high dilutions in many field situations, such as environmental management, 24 organic agriculture 25 and in herd, broiler, and fish breeding, with a view to improving productivity. [26][27][28][29][30][31][32][33][34] The aim of the current study was to explore whether the solvatochromic dye methylene violet (MV) could be used as a molecular detector of high dilutions in large water reservoirs, using phosphorus 30cH as a seeding solution.…”
Section: Introductionmentioning
confidence: 99%